2023
DOI: 10.1111/gcb.16568
|View full text |Cite
|
Sign up to set email alerts
|

Nitrification, denitrification, and related functional genes under elevated CO2: A meta‐analysis in terrestrial ecosystems

Abstract: Global change may have profound effects on soil nitrogen (N) cycling that can induce positive feedback to climate change through increased nitrous oxide (N2O) emissions mediated by nitrification and denitrification. We conducted a meta‐analysis of the effects of elevated CO2 on nitrification and denitrification based on 879 observations from 58 publications and 46 independent elevated CO2 experiments in terrestrial ecosystems. We investigated the effects of elevated CO2 alone or combined with elevated temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…Such results are in line with a previous study that found that CO 2 enrichment significantly decreased N 2 O emissions by 22% in global paddy soils 60 but contrasted with most meta-analysis studies reporting a stimulation of soil N 2 O emissions by CO 2 enrichment in terrestrial ecosystems. 25,61,62 The effect of CO 2 enrichment on soil N 2 O emissions may vary depending on the ecosystem. For instance, elevated CO 2 caused a nonsignificant increase in soil N 2 O emissions in terrestrial ecosystems but a significant increase in soil N 2 O emissions in fertilized upland soils and in natural wetlands.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such results are in line with a previous study that found that CO 2 enrichment significantly decreased N 2 O emissions by 22% in global paddy soils 60 but contrasted with most meta-analysis studies reporting a stimulation of soil N 2 O emissions by CO 2 enrichment in terrestrial ecosystems. 25,61,62 The effect of CO 2 enrichment on soil N 2 O emissions may vary depending on the ecosystem. For instance, elevated CO 2 caused a nonsignificant increase in soil N 2 O emissions in terrestrial ecosystems but a significant increase in soil N 2 O emissions in fertilized upland soils and in natural wetlands.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on natural and seminatural ecosystems like grasslands have indicated that elevated CO 2 affects N 2 O emissions depending on their effects on denitrification-derived N 2 O emission. ,, Under warming, nonsignificant increases in nitrification-derived and total N 2 O emissions have been reported in a Tibetan alpine meadow . However, such results cannot be extrapolated to agricultural ecosystems with large N fertilizer inputs and highly anthropogenic disturbances because of the different responses to soil properties associated with N transformations to elevated CO 2 and warming under more intensive agriculture. ,, For example, the response of soil inorganic N to warming is significantly higher in cropland than in grassland and shrubland . Complicating things further, these responses to multiple factors might not be predicted by simple linear extrapolations from single-factor studies because multifactor responses are frequently nonadditive and even counteractive. ,,, For instance, warming notably decreased soil organic matter at ambient CO 2 conditions while leading to a negligible effects at elevated CO 2 level, suggesting a significant interaction between elevated CO 2 and warming .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Denitrification (NO 3 − ‐N → NO 2 − ‐N → NO→N 2 O → N 2 ), a key link in the N cycle, is an important pathway resulting in the loss of available N in soils (Attard et al, 2011; Lan et al, 2023; Z. Li, Tang, et al, 2021; Z. Li, Tiang, et al, 2021). Nitrite reductase‐mediated reduction of NO 2 ‐ to NO is the central step in denitrification because dissolved N becomes gaseous N for the first time (Gineyts & Niboyet, 2023; Yang et al, 2017; Yin et al, 2014). Currently, nitrite reductase marker genes ( nirK and nirS ) are routinely used, enabling us to reveal the abundance and structure of denitrifying microbes in soil samples.…”
Section: Introductionmentioning
confidence: 99%
“…Li, Tiang, et al, 2021). Nitrite reductase-mediated reduction of NO 2 -to NO is the central step in denitrification because dissolved N becomes gaseous N for the first time (Gineyts & Niboyet, 2023;Yang et al, 2017;Yin et al, 2014). Currently, nitrite reductase marker genes (nirK and nirS) are routinely used, enabling us to reveal the abundance and structure of denitrifying microbes in soil samples.…”
mentioning
confidence: 99%